2021
DOI: 10.1136/bcr-2021-245350
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced autoimmune haemolytic anemia in a patient with chronic lymphocytic leukaemia successfully treated with ibrutinib

Abstract: We present a unique case of a patient with a long-standing history of indolent chronic lymphocytic leukaemia (CLL) who suddenly developed autoimmune haemolytic anaemia after starting immune checkpoint inhibitor therapy for bladder cancer. He had no clear indication to start CLL-directed treatment based on current clinical practice guidelines; however, targeted treatment of CLL with ibrutinib proved to be effective in treating the haemolytic anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A review by Tanios et al demonstrated that the first report on Pem-induced hematologic toxicity was published in 2014. 7 Subsequently, as the indications for Pem have increased, including malignant melanoma, 15,16 non-small cell lung cancer, 17,18 and chronic lymphocytic leukemia, 19 there have been increased in reports of hemolytic anemia as an irAE. Pem is available for renal cell carcinoma and UC; Funabashi et al reported real-life a clinical practice study that demonstrated that grade 3 or higher anemia occurred in 2.9% of patients with advanced UC refractory to cisplatin, 20 with a short mean follow-up of 7.7 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Tanios et al demonstrated that the first report on Pem-induced hematologic toxicity was published in 2014. 7 Subsequently, as the indications for Pem have increased, including malignant melanoma, 15,16 non-small cell lung cancer, 17,18 and chronic lymphocytic leukemia, 19 there have been increased in reports of hemolytic anemia as an irAE. Pem is available for renal cell carcinoma and UC; Funabashi et al reported real-life a clinical practice study that demonstrated that grade 3 or higher anemia occurred in 2.9% of patients with advanced UC refractory to cisplatin, 20 with a short mean follow-up of 7.7 months.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the first report on Pem‐induced hematologic toxicity was published in 2014. 7 Subsequently, as the indications for Pem have increased, including malignant melanoma, 15 , 16 non‐small cell lung cancer, 17 , 18 and chronic lymphocytic leukemia, 19 there have been increased in reports of hemolytic anemia as an irAE. Pem is available for renal cell carcinoma and UC; Funabashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of HLH in adults is based on the HLH-94 protocol, which proposes an initial combination of dexamethasone with etoposide and later association of cyclosporine A. A recent general recommendation for the treatment of different entities Cases of ir-AIHA in patients with a concurrent solid malignancy and CLL Resolution AIHA, auto-immune hemolytic anemia; CLL, chronic lymphocytic leukemia; DAT, direct antigen test; HLH, hemophagocytic lymphohistiocytosis; ICI, immune checkpoint inhibitor; irAE, immune-related adverse event; mMel, metastatic melanoma; mNSCLC, metastatic non-small cell lung cancer; mSCC, metastatic squamous cell cancer Ipi, ipilimumab; Nivo, nivolumab; Pembro, pembrolizumab [3,7,[11][12][13][14]. of HLH, including those related to immunotherapies, states that interruption of the treatment and corticosteroids might be sufficient for ir-HLH based on a number of case reports, but association of tocilizumab can be considered in analogy with CAR-T cell-induced CRS [31].…”
Section: Hemophagocytic Lymphohistiocytosismentioning
confidence: 99%
“…The drugs most commonly reported include second and third-generation cephalosporins, cotrimoxazole, NSAIDs, oxaliplatin, and fludarabine. 5,6 There are some reports of new drugs causing DIIHA recently, such as the immune checkpoint inhibitors pembrolizumab 7 and atezolizumab. 8,9 Eight hundred-two new medications were approved during the calendar year 2022.…”
Section: Introductionmentioning
confidence: 99%